2007
DOI: 10.1002/eqe.777
|View full text |Cite
|
Sign up to set email alerts
|

On the response of yielding seismically isolated structures

Abstract: SUMMARYThis paper investigates the seismic response of yielding isolated structures. To establish a general understanding of the nonlinear response of seismically isolated structures, this study first investigates the nonlinear response of isolated structures subjected to steady-state harmonic motion and nonlinear transient ground excitation. The response of both viscously damped and hysteretically damped isolation systems is investigated in three phases. Initially, basic insights are gained through simple non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
31
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
(6 reference statements)
2
31
0
2
Order By: Relevance
“…The intuitive assumption that superior performance of an isolated building in a design event naturally leads to superior performance in other earthquake scenarios deserves critical examination. Yielding of the isolated superstructure in extreme events is likely and the associated response trends have been examined by many [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The intuitive assumption that superior performance of an isolated building in a design event naturally leads to superior performance in other earthquake scenarios deserves critical examination. Yielding of the isolated superstructure in extreme events is likely and the associated response trends have been examined by many [7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…, Kikuchi et al . , and Thiravechyan et al . indicate that inelastic deformation of base‐isolated structures, if it occurs, may be much larger than expected.…”
Section: Introductionmentioning
confidence: 98%
“…Constantinou and Quarshie [4], Ordonez et al [5], Kikuchi et al [6], Thiravechyan et al [7] and Cardone et al [8] investigated the response of inelastic seismically isolated structures and agreed that allowing base-isolated superstructures to yield requires careful consideration because of possible occurrence of large ductility demands. Vassiliou et al [9][10][11] concluded that designing typical seismically isolated structures to behave elastically, as prescribed by current seismic design codes, is not overly conservative but a necessity that emerges from the fundamental dynamics of such structures.…”
Section: Introductionmentioning
confidence: 99%